Intradural Spinal Cord Stimulation: Performance Modeling of a New Modality - Anderson, David J.; Kipke, Daryl R.; Nagel, Sean J.; Lempka, Scott F.; Machado, Andre G.; Holland, Marshall T.; Gillies, George T.; Howard, Mathew A.; Wilson, Saul (Frontiers in Neuroscience, 2019)
Introduction: Intradural spinal cord stimulation may offer significant therapeutic benefits for those with intractable axial and extremity pain, visceral pain, spasticity, autonomic dysfunction and related disorders. A novel intradural electrical stimulation device, limited by the boundaries of the thecal sac, CSF and spinal cord was developed to test this hypothesis. In order to optimize device function, we have explored finite element modeling. Methods: COMSOL® Multiphysics Electrical Currents was used to solve for fields and currents over a geometric model of a spinal cord segment. Cathodic and anodic currents are applied to the center and tips of the T-cross component of the electrode array to shape the stimulation field and constrain charge-balanced cathodic pulses to the target area. Results: Currents from the electrode sites can move the effective stimulation zone horizontally across the cord by a linear step method, which can be diversified considerably to gain greater depth of penetration relative to standard epidural spinal cord stimulation. It is also possible to prevent spread of the target area with no off-target action potential. Conclusions: Finite element modeling of a T-shaped intradural spinal cord stimulator predicts significant gains in field depth and current shaping that are beyond the reach of epidural stimulators. Future studies with in vivo models will investigate how this approach should first be tested in humans.